Genotoxic properties of representatives of alkylindazoles and aminoalkyl-indoles which are consumed as synthetic cannabinoids. (June 2015) - Koller, Verena J.; Ferk, Franziska; Al-Serori, Halh; Mišík, Miroslav; Nersesyan, Armen; Auwärter, Volker; Grummt, Tamara; Knasmüller, Siegfried
Highlights: Synthetic cannabinoids (SCs) are marketed as a surrogate of marijuana. The genotoxic properties of four SCs (AM2201, UR144, 5F-AKB-48, AM2201-IC) were investigated. Positive results were found in comet assays and in micronucleus assays with human lymphocytes. Negative results were obtained in bacterial mutagenicity tests. The findings indicate that SCs cause DNA damage and possibly adverse health effects in users. Abstract: Synthetic cannabinoids (SCs) cause similar effects as cannabis and are sold in herbal mixtures. Recent investigations indicate that some of these drugs possess genotoxic properties. Therefore, we tested representatives of two groups, namely, aminoalkylindoles (AM-2201 and UR-144) and 1-alkylindazoles (5F-AKB-48 and AM-2201-IC) in single cell gel electrophoresis and micronucleus (MN) assays with human lymphocytes and in Salmonella/microsome assays. All drugs except AM-2201 caused DNA-migration, the LOELs were between 50 and 75 µM. Furthermore, all SCs caused inhibition of cell division and significant induction of MN which reflect structural and numerical chromosomal aberrations. The LOEL values were 50 µM for UR-144 and 5-AKB-48 and 75 µM for the other drugs. Also the levels of nucleoplasmatic bridges which are formed from dicentric chromosomes were elevated under identical conditions while the frequencies of nuclear buds were not affected. These findings show that representatives of both groups cause chromosomal damage while the negative results in Salmonella assays (in strains TA98, TA100, TA1535, TA1537 and TA102) in absence and presence of metabolic activation indicate that they do not induce gene mutations. Taken together, these findings indicate that SCs may cause adverse health effects in users as a consequence of damage of the genetic material.